Interpretation of Lesya Ukrainka’s feerie drama in the Panel Painting by R. Petruk, “Forest Song”. School of M. Storozhenko - Tarasenko, Andrii; Tarasenko, Olga (Art and Design, 2025)
The study aimed to reveal the individual interpretation of Lesya Ukrainka’s drama-feerie in the painting by R. Petruk “Forest Song”. Hermeneutical, comparative, iconographic, iconological, historical and cultural methods were used. The correlation between the content of the drama and the mythopoetics of the pictorial image was analysed. The panel painting was studied concerning the theme of earthly and heavenly love in world art. The study analysed the nature of personification of images of natural elements; the conventionality of pictorial and spatial solutions; and the role of attributes in the creation of artistic images. The importance of the heritage of Ukrainian Baroque and world monumental, decorative and easel art in the creation of the personal style of the work was investigated. The compositional and plastic solution of the canvas was analysed. The creative method of R. Petruk was studied in the context of the school of M. Storozhenko and the National Academy of Fine Arts and Architecture. The study revealed the relationship between the metaphysical nature of Mr R. Petruk’s painting “Forest Song” and the nature of Volyn. The innovative approach to creating a synthetic image of a drama-feerie by visual means was demonstrated. The individual nature of perception and interpretation of a literary work was highlighted. The traditions of national and world art, on which the artist relies, were revealed. The key role of the flute in the symbolism of the panel painting was demonstrated; the leading role of music in the harmony of the universe was determined. The author revealed the deep interconnection of the images of Lukash, Mavka, and Lesya Ukrainka with the mythological hero Orpheus. The study traced the common features of Mr. Petruk’s painting with the theatre curtain and the Baroque iconostasis. The study emphasised that the peculiarity of R. Petruk’s composition is the monumental and decorative mode. The study results are relevant for teachers and students of artistic educational institutions, in lecture courses on the history of Ukrainian art and music culture; for artists, cultural critics and art historians in creating a history of contemporary monumental and decorative art.